2022
DOI: 10.1002/pol.20210874
|View full text |Cite
|
Sign up to set email alerts
|

Microgels as drug carriers for sonopharmacology

Abstract: The ultrasound‐induced cleavage of covalent and non‐covalent bonds to activate drugs (sonopharmacology) is a promising concept to gain control over the action of active pharmaceutical ingredients by an external trigger. Previously, linear polymer architectures bearing drug payloads were exploited for drug release by using the principles of polymer mechanochemistry. In this work, the carrier design is altered by the polymer topology to improve the ultrasound‐triggered release of covalently anchored drugs from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Recently, covalently connected mechanophores have also been used to develop a mechanoresponsive carrier system for the release of cargo molecules from microgels. 137 The mechanophores have been incorporated alongside latent drugs into linear copolymers, which then formed microgels upon crosslinking with mechanoresponsive disulfides. It has been shown that the ultrasound-induced disulfide scission generates free thiols in the system initiating an intramolecular release cascade reaction.…”
Section: Functional Force-responsive Microgelsmentioning
confidence: 99%
“…Recently, covalently connected mechanophores have also been used to develop a mechanoresponsive carrier system for the release of cargo molecules from microgels. 137 The mechanophores have been incorporated alongside latent drugs into linear copolymers, which then formed microgels upon crosslinking with mechanoresponsive disulfides. It has been shown that the ultrasound-induced disulfide scission generates free thiols in the system initiating an intramolecular release cascade reaction.…”
Section: Functional Force-responsive Microgelsmentioning
confidence: 99%
“…To solve this problem, microgels were investigated as drug carriers instead of linear polymers. 74 Microgels are colloidally dissolved networks with a size of several hundred nanometres, and have been reported to be extremely sensitive to external force stimuli. 75 Perhaps due to their bulkier sizes compared with polymer chains in solutions, stimuli like sonication could generate greater forces in microgels.…”
Section: Mechanical Release Of Drugsmentioning
confidence: 99%
“…On the other hand, mechanophores were incorporated into polymer structures for which the topology drastically increased the mechanochemical reactivity and thereby decreased the necessary ultrasound doses. For example, this was achieved by designing mechanochemically responsive ultrahigh molar mass polyaptamers as supramolecular groups to inhibit the activity of bioactives, , gold nanoparticle assemblies, , genetically engineered proteins, microgels, and polymer brushes . Consequently, sonication times using a classical immersion probe sonicator at 20 kHz could be reduced by 1–2 orders of magnitude, i.e., from hours to seconds.…”
Section: Sonopharmacologymentioning
confidence: 99%